2021
DOI: 10.1002/ppul.25028
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐disordered breathing in cystic fibrosis

Abstract: Sleep‐disordered breathing (SDB) is an under recognized comorbidity in the cystic fibrosis (CF) population across the lifespan. Nocturnal hypoxemia, obstructive sleep apnea, and nocturnal hypoventilation are respiratory abnormalities that occur commonly during sleep in patients with lung disease, and have deleterious consequences to the quality of life in people with CF. Effective screening for these abnormalities is needed to allow for timely initiation of treatment, which has been reported to be efficacious.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 116 publications
(170 reference statements)
0
5
0
Order By: Relevance
“…Although the AHI of the entire population in this study was normal, consistent with existing literature [ 13 , 21 , 24 , 32 ], there was a high prevalence of OSA (AHI ≥ 5/h). Comparing our data with the available literature is challenging, because study designs and patient selection are heterogenous with respect to age, lung function, BMI and sample size, and PSG studies examining an exclusively adult CF population are rare [ 7 , 33 ]. Published data regarding the prevalence of OSA in adult pwCF report a prevalence of 3.2–3.9% [ 13 , 32 ], substantially lower than the 40% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the AHI of the entire population in this study was normal, consistent with existing literature [ 13 , 21 , 24 , 32 ], there was a high prevalence of OSA (AHI ≥ 5/h). Comparing our data with the available literature is challenging, because study designs and patient selection are heterogenous with respect to age, lung function, BMI and sample size, and PSG studies examining an exclusively adult CF population are rare [ 7 , 33 ]. Published data regarding the prevalence of OSA in adult pwCF report a prevalence of 3.2–3.9% [ 13 , 32 ], substantially lower than the 40% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep-disordered breathing (SDB) encompasses OSA which is due to intermittent collapse of the upper airway during sleep, central sleep apnea (CSA) which is due to the intermittent absence of respiratory effort during sleep, as well as hypoventilation, which may occur in persons with CF from various mechanisms. 11,12 Early studies often reported on SDB without differentiating between SDB patterns and since OSA is the most common SDB pattern, the term OSA will be used in describing these studies. 13,14 The intermittent collapse of the upper airway during sleep in OSA leads to breathing pauses and may cause oxygen desaturation and sleep fragmentation.…”
Section: Obstructive Sleep Apnea (Osa)mentioning
confidence: 99%
“…Furthermore, different from patients with bronchiectasis and mycobacterial infections, patients with CF often manifest poor sleep quality with frequent awakenings and daytime sleepiness, and such disturbances are more frequent with the progression of the disease [ 68 ]. Despite this, SDB prevalence is still under-recognized in this population of patients and may impact disease outcomes [ 69 ]. As an example, in CF patients with a severe disease complicated by pulmonary hypertension and right ventricular failure, chronic nocturnal hypoxia secondary to untreated SDB may worsen the disease leading to a poor prognosis [ 70 ].…”
Section: Sleep-disordered Breathing and Cystic Fibrosismentioning
confidence: 99%